Lifelong learning: the référentiel of the Bologna Process in Portugal - Palma, Albertina (2020)
The article is focused on the cognitive and normative framework (référentiel) behind the Bologna Process and on how this European référentiel was edited and disseminated in Portugal by the Portuguese mediators. This is part of a broad study, which analyses the implementation of the Bologna Process in Portugal, in the first decade of the twenty first century. The study adopted the public action approach in the analysis of political decision, which helped focus attention on the multilevel multiple actors of the BP, as well as on their contexts and modes of interaction, and mobilized the concepts of référentiel and edition. An interpretative descriptive study was conducted, based on content analysis of documents mostly retrieved from the Internet, by using a mixed deductive and inductive method. The aim was to identify and learn about the cognitive and normative frameworks of the key actors, who functioned as mediators, and analyze how these influenced the interpretations and edition of the European référentiel, which those actors disseminated in the Portuguese context. Results suggest that the Portuguese mediators edited the European Bologna Process référentiel of knowledge-based competitive economy, around the Lifelong Learning "paradigm". This référentiel of lifelong learning circulated through opinion documents and lies behind the legislation that frames the Bologna Process in Portugal.